Analysis of the Relationship Between Age and Acute Respiratory Infection Claim Costs in the Health Insurance Program of PT XYZ - Anggun Nabila; Dwi Nurmawaty (Sean Institute, 2026)
The frequency of health insurance claims in corporate insurance systems continues to increase, making the understanding of case characteristics and cost determinants essential for effective health risk management. This study aims to analyze the characteristics of patients with acute respiratory infection (ARI) and to examine the relationship between age and health insurance claim costs, measured by total charges and approved costs. A quantitative approach with a cross-sectional design was applied using secondary data from 401 health insurance claims at PT XYZ, including 46 ARI cases. Data normality was assessed using the Shapiro–Wilk test, and bivariate analysis was conducted using Spearman’s rho correlation. The proportion of ARI cases accounted for 11.5% of all claims, with children representing the largest group of patients. The results indicate a significant negative correlation between age and total claim costs (r = −0.350; p = 0.017) as well as approved costs (r = −0.316; p = 0.032). These findings suggest that younger age groups, particularly children, tend to incur higher claim costs compared to older age groups. However, given the limited number of ARI cases, the results should be interpreted with caution and cannot be broadly generalized. Further studies with larger sample sizes and additional explanatory variables are recommended to strengthen the evidence base for health insurance risk management.